Systematic interventions based on the stress-induced situation, affective, bodily, and cognitive reactions framework to mitigate psychological distress in lung cancer patients post-thoracoscopic surgery: a randomized clinical trial - Tang, Lili; Liu, Quan-Xing; He, Yuexia; Peng, Huanzhi; Luo, Maoyu; Zheng, Hong; Zhang, Qingling (Frontiers in Psychology, 2025)
ObjectiveTo evaluate the efficacy of a multi-component intervention based on the Situational, Affective, Bodily, and Cognitive (SABC) stress-response model in reducing psychological distress and enhancing quality of life among post-thoracoscopic lung-cancer patients.MethodsIn this single-center, assessor-masked, parallel-group randomized controlled trial, 240 patients were randomized (1:1) to either a 12-month SABC intervention (n = 120) or standard care (n = 120) by means of computer-generated, sealed-envelope allocation. Outcome assessors were blinded to group assignment. The intervention comprised psycho-education, SABC-based skills training, a daily-habits checklist and scheduled follow-up. Psychological distress was measured with the NCCN Distress Thermometer (DT); quality of life was assessed with the EORTC QLQ-C30 at baseline and at 1, 3, 6, and 12 months post-surgery. Linear mixed-effects models were used, under both intention-to-treat (ITT) and per-protocol analyses, to test time-by-group interactions.ResultsTime-by-group interactions favored the intervention group for physical (ITT: F = 5.632, P < 0.001; PP: F = 6.084, P < 0.001), role (ITT: F = 3.325, P = 0.010; PP: F = 2.675, P = 0.031) and emotional functioning (ITT: F = 5.543, P < 0.001; PP: F = 5.566, P < 0.001), and for the distress thermometer (ITT: F = 3.791, P = 0.005; PP: F = 5.258, P < 0.001). Social functioning improved in the ITT analysis only (P = 0.016); fatigue improved in the per-protocol analysis only (P = 0.008). No significant differences were observed for cognitive functioning, nausea and vomiting, pain, dyspnoea, insomnia, appetite loss, constipation, diarrhea, financial difficulties or global health status (P > 0.05).ConclusionA structured SABC-informed intervention significantly improves functional domains and reduces psychological distress in early-stage lung-cancer survivors after thoracoscopic surgery. Limitations include recruitment from a single tertiary center and exclusion of patients with severe comorbidities, which may limit generalisability to broader clinical populations.Clinical Trial RegistrationA randomized controlled trial of a psychological-distress intervention in patients with lung cancer based on the SABC framework. https://www.chictr.org.cn/searchproj.html?title=&officialname=&subjectid=&regstatus=&regno=ChiCTR1900028487&secondaryid=&applier=&studyleader=&createyear=&sponsor=&secsponsor=&sourceofspends=&studyailment=&studyailmentcode=&studytype=&studystage=&studydesign=&recruitmentstatus=&gender=&agreetosign=&measure=&country=&province=&city=&institution=&institutionlevel=&intercode=&ethicalcommitteesanction=&whetherpublic=&minstudyexecutetime=&maxstudyexecutetime=&btngo=btn, identifier: ChiCTR1900028487.